Solid-State Polymerization of Semiaromatic Copolyamides of Nylon-4,T and Nylon-4,6: Composition Ratio Effect and Thermal Properties - Kim, Young Jun; Yohana, Kurnia Endah; Lee, Hong-shik; Kim, Jaehoon (AMER CHEMICAL SOC, 2012)
Solid-state polymerization (SSP) of semiaromatic copolyamides composed of nylon-4,T and nylon-4,6 in different molar ratios were investigated using a mixture of nitrogen and steam as the sweep fluid at reaction temperatures in the range of 220-260 degrees C. Prepolymers having different nylon-4,T contents (28.2, 37.9, and 47.8 mol %) were synthesized by melt polyamidation with stoichiometric ratios of diamine and diacid. The SSP conditions were carefully chosen to eliminate the influences of both internal and external diffusion of the reaction byproducts. Under these conditions, a high-molecular-weight semiaromatic copolyamide with an intrinsic viscosity of 2.469 dL/g was obtained upon SSP at 260 degrees C for 48 h. As the nylon-4,T content increased, the SSP rate decreased owing to the inherently low reactivity of the aromatic diacid and inhibition of chain-end mobility. The glass transition, melting, and decomposition temperatures of the polymers synthesized from the higher-nylon-4,T-content prepolymer were always higher than those of the polymers synthesized from the lower-nylon-4,T-content prepolymer.
Keywords: HIGH-MOLECULAR-WEIGHT; BISPHENOL-A POLYCARBONATE; REACTION-KINETICS; POLY(L-LACTIC ACID); MELT/SOLID POLYCONDENSATION; MORPHOLOGICAL CONSEQUENCES; COMPREHENSIVE MODEL; EQUILIBRIUM-MODEL; SWEEP FLUID; POLY(ETHYLENE-TEREPHTHALATE)